Degradation Rate Model Formulation to Estimate Soil Carbon Sequestration from Repeated Biosolids Application. Issue 1 (30th January 2014) - Zhai, Wenjuan; Moschandreas, Demetrios J.; Tian, Guanglong; Venkatesan, Dhesikan; Noll, Kenneth E.
Abstract : Land application of biosolids is a process that increases the amount of soil C sequestration and may produce C credits in accordance with the definition of United Nations Climate Change Convention. A dynamic degradation rate model (DRM) provides insights on C sequestration due to microbial biomass, soil organic carbon (SOC), CO2 emission rates, residence time of sequestered C, and biomass to biosolids ratios. We employed a 34‐yr biosolids application database from the literature to determine the amount of C sequestered in 41 strip‐mined Illinois fields. This database is used to formulate the DRM using curve fitting techniques. Degradation rate model applications identify two SOC phases in soil. Soil organic C gain in Phase 1 (first 10 yr) is primarily due to biosolids application while in Phase 2, SOC gain is due to biomass or C sequestration. Carbon sequestration changes with time relate to variations in biosolids application amounts (10 and 18 Mg ha ‐1 yr ‐1 ), different degradation rate constants (0.04–0.16 yr ‐1 ), and biomass yields (35–40%). Additionally, the degradation rate constant is correlated positively with the C application rate for a period of 34 yr. Based on the 34‐yr database, the DRM simulates the process that decomposes SOC produced by biosolids application into C in biosolids that have not been degraded and C in biomass produced during the microbial degradation process. The DRM quantifies the biosolids degradation rate constant and biomass yield, and provides an easy quantitative method for evaluating C credits from biosolids added to soil.